1995
DOI: 10.1002/ajmg.1320600102
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the APOE locus influences rate of disease progression in late onset familial Alzheimer's Disease but is not causative

Abstract: An association has been observed in several independent data sets between late onset Alzheimer's Disease (AD) and the APOE locus on chromosome 19. We have examined the genotype in family history positive (FHP) and family history negative (FHN) cases and find a distortion of the APOE allele frequencies in accord with previous studies. However, when we examined the allele distribution of the at-risk siblings of the FHP group we found an excess of the epsilon 4 allele which also differs significantly from histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…This earlier age of onset is a consistent finding associated with apoE ⑀4/4 (Corder et al, 1993;Soininen, 1995). Other studies, furthermore, have reported on a more rapid progression of the disease in these patients (Bennett et al, 1995). These findings implicate that patients with apoE ⑀4 alleles might reach more advanced stages of the disease at a younger age than patients without ⑀4.…”
Section: Apoe Genotype and Stage Dependency Of Reparative Capacitysupporting
confidence: 81%
See 1 more Smart Citation
“…This earlier age of onset is a consistent finding associated with apoE ⑀4/4 (Corder et al, 1993;Soininen, 1995). Other studies, furthermore, have reported on a more rapid progression of the disease in these patients (Bennett et al, 1995). These findings implicate that patients with apoE ⑀4 alleles might reach more advanced stages of the disease at a younger age than patients without ⑀4.…”
Section: Apoe Genotype and Stage Dependency Of Reparative Capacitysupporting
confidence: 81%
“…It has been shown recently that the ⑀4 allele is a major risk factor for late-onset familial AD and probably also for sporadic AD (Corder et al, 1993;Mayeux et al, 1993;Poirier et al, 1993b;Rebeck et al, 1993;Saunders et al, 1993;Strittmatter et al, 1993a). Moreover, AD patients with ⑀4 alleles usually show an earlier age of onset (Corder et al, 1993;Basun et al, 1995;Locke et al, 1995) and a more rapid progression of the disease (Bennett et al, 1995), suggesting a causal link between apoE polymorphism and the development of AD (for review, see Roses et al, 1994).…”
Section: Abstract: Alzheimer's Disease; Apolipoprotein E; Degeneratimentioning
confidence: 99%
“…mRNA for Srebf1 (sterol regulatory element binding factor 1), implicated in lipogenic gene expression (33), was down-regulated in ␥3 R225Q mutant mice, whereas mRNA encoding for Ppargc1a (peroxisome proliferative-activated receptor, ␥ coactivator 1 ␣), known to increase the expression of both nuclear and mitochondrial-encoded genes of oxidative metabolism (34), was up-regulated. Additionally, a key gene integral to free fatty acid uptake (Cd36 (35)), as well as genes involved in use of fat-derived energy (3-oxoacid-CoA transferase 1, Oxct1, EC 2.8.3.5 and carboxylesterase 3, Ces3, EC 3.1.1.1) were up-regulated in TgPrkag3 225Q mice.…”
Section: ␥3-containing Ampk Heterotrimers Regulate Lipid Metabolism Gmentioning
confidence: 99%
“…A great deal of interest has been generated concerning the role of the ApoE as a risk factor for AD and an association between late-onset AD and the ApoE locus on chromosome 19 (Roses, 1994;Bennett, 1995;Cacabelos, 1996;Cacabelos et al, 1996), has been recently observed. Apolipoprotein E is a secretory glycoprotein and the three common allelic isoforms of this protein (ApoE 2, ApoE 3, and ApoE 4) are associated with distinct patterns of lipoprotein metabolism and variable risks for coronary artery disease (Tiret, 1994), raising the possibility that a dysfunction of the lipid transport system could seriously affect lipid homeostasis in the brain.…”
Section: Introductionmentioning
confidence: 99%